A Combination of Metal and Organic Catalysis: Highly Diastereo‐ and Enantioselective Construction of Fluorinated 2‐Aminocyclopenta[b]pyran Derivatives. Issue 16 (29th October 2015) - Peng, Jiahuan; Zhao, Bo‐Liang; Du, Da‐Ming
Abstract: An efficient highly diastereo‐ and enantioselective protocol to access optically pure fluorine‐containing 2‐amino‐cyclopenta[ b ]pyran derivatives using Lewis acid catalysis and organocatalysis sequence has been developed. The corresponding products could be obtained in good to excellent yields with good to excellent diastereoselectivity and enantioselectivity (up to 99:1 dr, >99% ee ). Abstract :